2012
DOI: 10.1002/chem.201200010
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design and Synthesis of Optimized Glycoclusters for Multivalent Lectin–Carbohydrate Interactions: Influence of the Linker Arm

Abstract: The design of multivalent glycoclusters requires the conjugation of biologically relevant carbohydrate epitopes functionalized with linker arms to multivalent core scaffolds. The multigram-scale syntheses of three structurally modified triethyleneglycol analogues that incorporate amide moiety(ies) and/or a phenyl ring offer convenient access to a series of carbohydrate probes with different water solubilities and rigidities. Evaluation of flexibility and determination of preferred conformations were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
124
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(135 citation statements)
references
References 70 publications
(125 reference statements)
10
124
0
1
Order By: Relevance
“…The tetrameric structure presents the binding sites in opposite orientation in space14b and therefore this particular lectin is also not very sensitive to multivalent effects 16. In the particular case of 21 , a significant decrease in affinity is even observed when compared to monovalent ligand α‐FucOMe thus suggesting that negative steric effects are certainly playing a role for the binding of fucose moieties of decavalent compound 21 to LecB.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…The tetrameric structure presents the binding sites in opposite orientation in space14b and therefore this particular lectin is also not very sensitive to multivalent effects 16. In the particular case of 21 , a significant decrease in affinity is even observed when compared to monovalent ligand α‐FucOMe thus suggesting that negative steric effects are certainly playing a role for the binding of fucose moieties of decavalent compound 21 to LecB.…”
mentioning
confidence: 98%
“…These compounds were compared to [2]rotaxanes 22 and 23 displaying only carbohydrate stoppers and to monovalent references β‐GalOMe (methyl‐β‐ d ‐galactopyranoside)14 and α‐FucOMe (methyl‐α‐ l ‐fucopyranoside) 15. The ITC data are summarized in Table 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been reported that novel mannoside glycolipid conjugates micelles are able to inhibit human immunodeficiency virus type 1 trans-infection mediated by human dendritic cells (Dehuyaser et al, 2012;Schaffer et al, 2013). Several multivalent galactosylated glycoclusters that incorporated analogues of triethyleneglycol as a linker arm were prepared (Cecioni et al, 2012). The selected structures comprised one or two amide groups, as well as phenyl aromatic ring, in a triethyleneglycol moiety to achieve increased rigidity of the chain.…”
Section: Resultsmentioning
confidence: 99%
“…24, 25). [61][62][63] Pieters et al reported bivalent galactosides which are thought to bind simultaneously to two of the four carbohydrate binding sites of LecA as concluded from the high potency (IC 50 = 220 nM). [64] LecB displays an unusually strong affinity for α-fucosides in the high nanomolar range, which could be explained by the crystal structure of the complex: [65] the presence of two calcium ions in the binding site and an additional lipophilic contact of the methyl group contribute to the strong binding.…”
Section: Ta Rgeting Quorum Sensingmentioning
confidence: 99%